2004
DOI: 10.1111/j.1742-7843.2004.pto_950405.x
|View full text |Cite
|
Sign up to set email alerts
|

The Presynaptic Activity of Bothropstoxin‐I, a Myotoxin from Bothrops jararacussu Snake Venom

Abstract: Bothropstoxin-I from Bothrops jararacussu snake venom is a lysine-49 phospholipase A 2 with myotoxic and neurotoxic activities. In this study, we used mouse phrenic nerve-diaphragm preparations in the absence and presence of manganese (Mn 2π ), a presynaptic blocker, to investigate a possible presynaptic action of bothropstoxin-I. At concentrations of 0.9 mM and 1.8 mM, Mn 2π produced 50% neuromuscular blockade in less than 4 min., which was spontaneously reversible at the lower concentration. Bothropstox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…BthTX-I is considered the main myotoxin from the venom since it is able to reproduce in vitro the neurotoxicity and the myonecrosis of the crude venom [43], being this characteristic the main reason of the interest in the myotoxin. BthTX-I has a presynaptic nature at 0.35 µM, which is not sufficient to cause muscle fiber depolarization [46]. The Asp49 to Lys49 substitution in the catalytic center (only in the calcium-binding loop) explains the lack of enzymatic action in BthTX-I, due to the loss of ability to bind Ca 2+ [47].…”
Section: Resultsmentioning
confidence: 99%
“…BthTX-I is considered the main myotoxin from the venom since it is able to reproduce in vitro the neurotoxicity and the myonecrosis of the crude venom [43], being this characteristic the main reason of the interest in the myotoxin. BthTX-I has a presynaptic nature at 0.35 µM, which is not sufficient to cause muscle fiber depolarization [46]. The Asp49 to Lys49 substitution in the catalytic center (only in the calcium-binding loop) explains the lack of enzymatic action in BthTX-I, due to the loss of ability to bind Ca 2+ [47].…”
Section: Resultsmentioning
confidence: 99%
“…Crude Bjssu venom induces neurotoxicity in vitro and causes muscle necrosis in vivo, resulting in irreversible tissue loss and limb amputation in severe accidents (29,30). Muscle necrosis is usually attributed to bothropstoxin-I, which is a myotoxic Lys49 PLA 2 homologue and the main toxic component of Bjssu venom (41). The myotoxic components of snake venoms can reduce the initiation of muscle contractures, muscle response after direct stimulation or elevated potassium exposure (42).…”
Section: Resultsmentioning
confidence: 99%
“…Oshima-Franco et al (2004) have shown that BthTX-I, at a concentration that does not produce neuromuscular blockade (0.35 mM) caused the appearance of giant miniature endplate potentials, without affecting the resting membrane potential. The authors suggested that the toxin would act through Ca 2+ channels, since Mn 2+ antagonized both neurotoxic and myotoxic actions of the myotoxin and are related to Ca 2+ fluxes.…”
Section: Pharmacologymentioning
confidence: 99%
“…Different mechanisms have been proposed for BthTX-I myotoxic effect such as altering the bilayer membrane integrity (Lomonte et al, 2003), binding to the Ca 2+ -binding region in the pore of Ca 2+ channels (Oshima-Franco et al, 2004), activating membrane acceptors (CintraFrancischinelli et al, 2009) or causing a general membrane-destabilizing (Gallacci & Cavalcante, 2009). In order to explain the rationale of this study more details will be given about these mechanisms.…”
Section: Pharmacology 578mentioning
confidence: 99%
See 1 more Smart Citation